Does oil price volatility impact on Nigeria's real sector? Evidence from ARDL Model - Jimoh Sina Ogede (Universitas Negeri Malang, 2020)
Oil price volatility and economic growth relation have been well established in the extant literature without reference to divergent across the countries and sectors. The underlying problem of how the effects of volatility in oil prices vary across economic sectors and how they may have evolved is of particular importance. This paper therefore discusses, using the autoregressive distributed lag model (ARDL), the effects of volatility in oil prices on the growth of the real sector in Nigeria. The results show that oil price volatility has a positive effect on the selected three real economic sectors (agriculture, manufacturing, and transport) in both the short and long term. Results demonstrate that changes in the real sector are subject to changes in oil prices and that shifts in crude oil prices have a positive and insignificant impact on the drive of each sector. Besides, the supply of money has an adverse and significant impact on the agriculture and transport sectors. Accordingly, the paper offers that the Nigerian government should employ the monetary and fiscal policies policy framework aiming at providing foreign investors with special offers to invest in agriculture; and need to offer interest-free loans and subsidies to the manufacturers, transporters, and farmers.